Fast atmospheric correction algorithm based on the darkest pixel approach for retrieving the aerosol optical thickness: comparison with in-situ AOT measurements - Themistocleous, Kyriacos; Alexakis, Dimitrios; Hadjimitsis, Diofantos G. (My University, 2011)
Darkest pixel atmospheric correction is the simplest and fully image-based correction method. This paper presents an overview of a proposed 'fast atmospheric correction algorithm' developed with MATLAB based on the RT equation basics and the darkest pixel approach. The task is to retrieve the aerosol optical thickness (AOT) from the application of this atmospheric correction. The effectiveness of this algorithm is assessed by comparing the AOT values from the algorithm with those measured in-situ both from MICROTOPS II hand-held sunphotometer and the CIMEL sunphotometer (AERONET)
Keywords: Aerosol optical thickness; Atmospheric correction; Darkest pixel method; Radiative transfer; Sunphotometer